Structures of deacetyl glykenins-a, b, and c, glycosidic antibiotics from basidiomycetes sp. - Fumiko Nishida (2018)
The structures of deacetyl Glykenins (DG)-A, B, and C, basic structures of Glykenins, were elucidated by chemical degradation and interpretation of spectral data. © 1988.